2016
DOI: 10.1021/jacs.6b03366
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Role of Imidazolium-Based Promoters for the Electroreduction of CO2 on a Silver Electrode

Abstract: The electrochemical reduction of CO2 to CO is a reaction of central importance for sustainable energy conversion and storage. Herein, structure-activity relationships of a series of imidazolium-based cocatalysts for this reaction are described, which demonstrate that the C4- and C5-protons on the imidazolium ring are vital for efficient catalysis. Further investigation of these findings led to the discovery of new imidazolium salts, which show superior activity as cocatalysts for the reaction, i.e., CO is sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
227
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(248 citation statements)
references
References 26 publications
20
227
1
Order By: Relevance
“…At the same time, the current-carrying ions are unlikely to be OH − or H + since in the case of a cation exchange membrane, the positively charged electrolyte cation, present in large excess, will flow from the anode to the cathode compartment, building up a cation concentration gradient since these ions are not electroactive. A similar phenomenon would occur for anion exchange membranes, where HCO 3 − ions are to be expected to carry the current. Furthermore, passive exchange of ions will occur across the membrane as long as their concentration is different in the two compartments.…”
Section: Bifunctional Catalysismentioning
confidence: 63%
See 1 more Smart Citation
“…At the same time, the current-carrying ions are unlikely to be OH − or H + since in the case of a cation exchange membrane, the positively charged electrolyte cation, present in large excess, will flow from the anode to the cathode compartment, building up a cation concentration gradient since these ions are not electroactive. A similar phenomenon would occur for anion exchange membranes, where HCO 3 − ions are to be expected to carry the current. Furthermore, passive exchange of ions will occur across the membrane as long as their concentration is different in the two compartments.…”
Section: Bifunctional Catalysismentioning
confidence: 63%
“…A number of products have been successfully synthesized by this process, most notably carbon monoxide (CO) [1][2][3] , formic acid (HCOOH), methane (CH 4 ) 4 , ethylene (C 2 H 4 ) 5 and ethanol (CH 3 CH 2 OH) 6 , as well as other compounds 7,8 . Due to the numerous possible reaction pathways, selectively targeting one specific product at high yield has remained a challenge, which, to the present day, has been achieved only for CO and formic acid in aqueous electrolytes.…”
mentioning
confidence: 99%
“…Therefore, the intermediates of CO 2 reduction must be adsorbed on the Ag surface37. It has been reported that Ag surfaces could stabilize anion radicals at certain negative potential depending on the experimental conditions, electrolyte and pH (standard redox potential for is −1.9 V)12363742. BDD can produce the anion radical in 0.1 M Na 2 SO 4 and this radical can be stabilized as an intermediate product under suitable experimental conditions (high pressure)30.…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of the interactions between the RTIL and the CO 2 ‐reducing catalyst can have a significant impact on the reduction product. Lau et al . examined the role of an imidazolium based RTIL on the reduction of CO 2 at a silver electrode.…”
Section: Introductionmentioning
confidence: 99%